Clinical profile, complications and outcome of scrub typhus in children: A hospital based observational study in central Nepal - Pathak, Santosh; Chaudhary, Nagendra; Dhakal, Prativa; Shakya, Disuja; Dhungel, Prativa; Neupane, Gagan; Shrestha, Sandeep; Regmi, Shanti; Kurmi, Om P. (PloS one, 2019)
Scrub typhus, an important cause of unexplained fever, is grossly neglected and often misdiagnosed in low and middle income countries like Nepal. The main aim of this study was to report on the clinical profile and complications of scrub typhus and its outcome in Nepalese children. A prospective observational study was carried out in children aged 1-16 years, admitted to a tertiary care hospital of central Nepal in between July 2016- Aug 2017. Scrub typhus was diagnosed with IgM ELISA. All cases of scrub typhus (n = 76) presented with fever and commonly had other symptoms such as headache (75%), myalgia (68.4%), vomiting (64.5%), nausea (59.2%), abdominal pain (57.9%), cough (35.5%), shortness of breath (22.4%), altered sensorium (14.5%), rashes (13.2%) and seizures (11.8%). Important clinical signs noticed were lymphadenopathy (60.5%), hepatomegaly (47.4%), edema (26.3%), jaundice (26.3%), and splenomegaly (15.8%). About 12% (n = 9) had necrotic eschar. Similarly, thrombocytopenia, raised liver enzymes and raised creatinine values were seen in 36.9%, 34.2% and 65.8% respectively. The most common complications were myocarditis (72.4%), hypoalbuminemia (71.1%), severe thrombocytopenia (22.4%), renal impairment (65.8%), hyponatremia (48.7%) and hepatitis (34.2%). Over two-thirds (69.70%) of the cases were treated with doxycycline followed by combination with azithromycin in the remaining 18.4%. Overall, mortality rate in this group was 3.9%. Scrub typhus should be considered as a differential in any community acquired acute undifferentiated febrile illness regardless of the presence of an eschar. Myocarditis and acute kidney injury are important complications which when addressed early can prevent mortality. Use of doxycycline showed a favorable outcome.